Toxic bachelors - Steel, Danielle (UK : Corgi Books, 2005)
They were the best of friends and the most daunting of bachelors - Charlie Harrington, Adam Weiss, and Gray Hawk. Now, the three friends, spending their summer vacation cruising the Mediterranean, are about to have their bachelorhoods rocked. For, as the once-carefree trio is about to discover, love is the most unpredictable adventure of all.
Keywords: v; Vacations -- Fiction. -- Mediterranean Region